A Novel Approach For Detection of Neurological Disorders through Electrical Potential Developed in Brain - Mohd Suhaib Kidwai; S. Hasan Saeed (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper talks about the phenomenon of recurrence and using this concept it proposes a novel and a very simple and user friendly method to diagnose the neurological disorders by using the EEG signals.The mathematical concept of recurrence forms the basis for the detection of neurological disorders,and the tool used is MATLAB.  Using MATLAB, an algorithm is designed which uses EEG signals as the input and uses the synchronizing patterns of EEG signals to determine various neurological disorders through graphs and recurrence plots